Sliding-mode control combined with improved adaptive feedforward for wafer scanner. (15th March 2018) - Li, Xiaojie; Wang, Yiguang
Highlights: The general form of an improved adaptive feedforward is proposed for nth-order systems with force ripple. The dominant frequency components of the force ripple are obtained by experimental analysis based on FFT. A sliding-mode control method combined with the improved adaptive feedforward is established for precision control of wafer scanner. The feasibility and effectiveness of the proposed methods are demonstrated by comparative experiments in real application. Abstract: In this paper, a sliding-mode control method combined with improved adaptive feedforward is proposed for wafer scanner to improve the tracking performance of the closed-loop system. Particularly, In addition to the inverse model, the nonlinear force ripple effect which may degrade the tracking accuracy of permanent magnet linear motor (PMLM) is considered in the proposed method. The dominant position periodicity of force ripple is determined by using the Fast Fourier Transform (FFT) analysis for experimental data and the improved feedforward control is achieved by the online recursive least-squares (RLS) estimation of the inverse model and the force ripple. The improved adaptive feedforward is given in a general form of nth-order model with force ripple effect. This proposed method is motivated by the motion controller design of the long-stroke PMLM and short-stroke voice coil motor for wafer scanner. The stability of the closed-loop control system and the convergence of the motion tracking are guaranteed by the proposed sliding-mode feedback and adaptive feedforward methods theoretically. Comparative experiments on a precision linear motion platform can verify the correctness and effectiveness of the proposed method. The experimental results show that comparing to traditional method the proposed one has better performance of rapidity and robustness, especially for high speed motion trajectory. And, the improvements on both tracking accuracy and settling time can be achieved.